Assessing offshore wind turbine reliability and availability. (February 2019) - Lazakis, Iraklis; Kougioumtzoglou, Maria A
The renewables sector and particularly offshore wind energy is a fast developing industry over the last few years. Especially, activities related to the installation, and operation and maintenance of offshore wind turbines become a challenging task with inherent risks. This article assesses the risks related to the above stages of a wind farm lifecycle using the failure mode, effects and criticality analysis and hazard identification methods. All works, from installation to operation and maintenance, are considered together with the wind turbine main components. An integrated risk analysis methodology is presented addressing personnel Safety (S), Environmental impact (E), Asset integrity (A), and Operation (O). The above is supplemented by a cost analysis with the aid of Bayesian belief networks method to assist the decision-making process related to installation, and operation and maintenance tasks. All major risks and critical wind turbine components are identified as well as measures are suggested to prevent or mitigate them. Moreover, inspection and maintenance plans are elaborated in general for the mentioned activities.